Resistance of freshwater sediment bacterial communities to salinity disturbance and the implication for industrial salt discharge and climate change-based salinization - Tammert, Helen; Kivistik, Carmen; Kisand, Veljo; Käiro, Kairi; Herlemann, Daniel P. R. (Frontiers in Microbiomes, 2023)
The impact of salinization on freshwater ecosystems became apparent during the 2022 ecological disaster in the Oder River, located in Poland and Germany, which was caused by salt discharge from mining activities. How bacterial communities respond to salinization caused by industrial salt discharge, or climate change-driven events, depends on the sensitivity of these complex bacterial communities. To investigate the sensitivity of bacterial communities to pulse salinization, we performed an experiment in the salinity range from 0.2 to 6.0. In addition, we sampled similar salinities in the littoral zone of the Baltic Sea where the bacterial communities are permanently exposed to the aforementioned salinities. To simulate a major disturbance, we included an ampicillin/streptomycin treatment in the experiment. Although the addition of antibiotics and increase in salinity had a significant impact on the water bacterial richness and community composition, only antibiotics affected the sediment bacterial community in the experiment. In contrast, sediment bacterial communities from the Baltic Sea littoral zone clustered according to salinity. Hence, sediment bacterial communities are more resistant to pulse changes in salinity than water bacteria but are able to adapt to a permanent change without loss in species richness. Our results indicate that moderate pulse salinization events such as industrial salt discharge or heavy storms will cause changes in the water bacterial communities with unknown consequences for ecosystem functioning. Sediment bacterial communities, however, will probably be unaffected in their ecosystem functions depending on the disturbance strength. Long-term disturbances, such as sea level rise or constant salt discharge, will cause permanent changes in the sediment bacterial community composition.